1992
DOI: 10.1007/bf00317248
|View full text |Cite
|
Sign up to set email alerts
|

The parasites of Anolis lizards in the northern Lesser Antilles

Abstract: The helminth communities from ten species of lizard on seven islands in the Caribbean were sampled by collecting one hundred specimens of each species. Nine genera of parasites were identified; these included six nematodes, two digeneans and an acanthocephalan. No relationship was discernible between parasite density or abundance and island area or altitude, although dry islands tend to have fewer species of parasites. Anolis lizards of the bimaculatus and wattsi series share similar parasites with four out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…Recently, there have been many records of encysted juveniles of Centrorhynchus spp. in the body-cavity and gut-wall of various species of Anolis, mostly from the Caribbean Region (Acholonu, 1976;Dobson et al, 1992;Goldberg et al, 1994Goldberg et al, , 1997aGoldberg et al, , b, 1998. Unfortunately, the specimens were identified only to generic level (as Centrorhynchus sp.)…”
Section: Remarksmentioning
confidence: 96%
“…Recently, there have been many records of encysted juveniles of Centrorhynchus spp. in the body-cavity and gut-wall of various species of Anolis, mostly from the Caribbean Region (Acholonu, 1976;Dobson et al, 1992;Goldberg et al, 1994Goldberg et al, , 1997aGoldberg et al, , b, 1998. Unfortunately, the specimens were identified only to generic level (as Centrorhynchus sp.)…”
Section: Remarksmentioning
confidence: 96%
“…[2][3][4][5][6][7][8]. For endangered mammals in protected areas, the only practical alternative to obtaining samples from culled individuals is fecal examination for parasite propagules (9), despite some limitations of this method (10).…”
mentioning
confidence: 99%
“…In a study of helminths occurring in skinks from Papua New Guinea, which has an area of 41.48 million hectares (Marshall and Beehler 2006) mean endoparasite species diversity per skink species was 5.0 ± 3.3 SD, range 1-11 (Goldberg et al 2010). However, Dobson et al (1992) found no relationship between parasite density/abundance and island area for Anolis lizards in the northern Lesser Antilles. Sample size may be an important determinant; from Table 1, with the exception of the sample from Agrigan Island, helminths were not found when sample size was 20 individuals or less.…”
Section: Discussionmentioning
confidence: 80%